Inventory of Tourism Assets on Department of Environment and Conservation Rangeland Properties - Smith, A.; Hughes, Michael; Wood, David; Glasson, John (CRC for Sustainable Tourism, 2008)
The project assessed the tourism potential of inland pastoral properties recently acquired by the Department of Conservation and Land Management (DEC) in the Murchison and Gascoyne regions of Western Australia. An inventory of natural and cultural tourism assets was compiled through desktop research and discussions with interest groups in the region. The report also includes perspectives on how the properties may afford a range of values both to DEC and the public good. The results of this project will help in the formulation of management approaches to tourism development on the DEC properties. The project will also facilitate development and strengthening of collaborative relationships between various tourism interest groups in the region.